METHOD OF PROJECTS IN EXTRACURRICULAR VOCAL AND CHORAL ACTIVITIES OF ADOLESCENTS (Pedagogy of Higher and Secondary Education, 2011)
Considering pedagogical and creative conditions of the organization of out-class and out-school activity of teenagers, in article we research a problem formation of art-creative requirements and orientations of lyceum students, applying a method projects by the exam of creative collectives - choir of Dolgincevsky humanities-technical liceum of Krivoi Rog and choir of  Novoivanivjska school.
Keywords: amateur creativity of teenagers; a parity pedagogical and creative educations of the organizations of the organization out-class and out-school activity; a method of projects; pedagogical designing